2015
DOI: 10.1186/s13052-015-0136-4
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal blood stream infections in tertiary referral hospitals in Kurdistan, Iran

Abstract: BackgroundBloodstream infection (BSI) is one of the most common causes of nosocomial infection in neonatal intensive care units (NICU). The aim of the present study was to determine bacterial agents and their susceptibility patterns to antibiotics and to investigate the risk factors associated with BSI.MethodsThis was a nested case–control study carried out from September 2009 to June 2010 in the NICU wards in Sanandaj hospitals western Iran. Cases were patients with BSI and controls were other patients who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
4
12
0
Order By: Relevance
“…Of note, PROM, active resuscitation required in labor room, TPN and MV were significant risk factors for early sepsis, but not for late sepsis. The most important neonatal factor predisposing to neonatal sepsis is prematurity and LBW [3]. Low birth weight and prematurity were major risk factors for early and late sepsis in our study.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Of note, PROM, active resuscitation required in labor room, TPN and MV were significant risk factors for early sepsis, but not for late sepsis. The most important neonatal factor predisposing to neonatal sepsis is prematurity and LBW [3]. Low birth weight and prematurity were major risk factors for early and late sepsis in our study.…”
Section: Discussionsupporting
confidence: 48%
“…Its prevalence rate in the present study was 2.7 per 1000 live births (94/30545) of 9.3 per 1000 neonatal admissions (94/10133). Nikkhoo et al [3] have reported a prevalence rate of 6.4% for sepsis. The prevalence of sepsis in their study was twice that of ours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitant with this, we also sought to specifically assess the current prevalence of neonatal bloodstream infections (BSIs) and current antimicrobial resistance (AMR) rates within the hospital to help target future intervention programs if BSIs are a concern. This is also a priority area across countries with up to ten million neonates worldwide dying within 5 days of birth, and most of these in LMICs due to BSIs [32,33]. Overall, up to 71% of neonates are prone to BSIs during intensive care, with neonatal infections contributing substantially to the morbidity and mortality of infants [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…(4,5) The spectrum of bacteria causing neonatal sepsis in the developing world is biased towards gram negative organisms as compared to the developed world where most of the cases involve group B streptococcus, E. coli and Listeria monocytogenes. (6,7,8,9) Klebsiella pneumoniae, Staphylococcus aureus and E. coli are the most common organisms causing neonatal sepsis both in-hospital and in-community settings in India followed by Acinetobacter species and Pseudomonas species. (2,5,10) The infants who survive the episode of neonatal sepsis are vulnerable to short-and long-term neurodevelopmental morbidity.…”
Section: Introductionmentioning
confidence: 99%